An engineered biomaterial to harness the differentiation potential of endogenous human gingival mesenchymal stem cells (hGMSCs) - Hasani-Sadrabadi, Mohammad Mahdi; Yuan, Weihao; Sevari, Sevda; Yu, Bo; Ansari, Sahar; Moshaverinia, Alireza (Frontiers in Dental Medicine, 2023)
Here, we developed a stromal cell-derived factor-1a (SDF-1 α) delivery biomaterial as an artificial polymeric-based niche with the ability to recruit local endogenous human gingival mesenchymal stem cells (hGMSCs) for craniofacial bone regeneration applications. Polydopamine-coated poly(ε-caprolactone) (PCL)-Gelatin electrospun membranes were loaded with stromal cell-derived factor-1 α (SDF-1α) via physical adsorption. Subsequently, the release profile of the SDF-1 α and chemotactic capacity on human bone marrow mesenchymal stem cells (hBMMSCs) and hGMSCs were evaluated. The osteogenic differentiation capacity of the recruited MSCs was also assessed in vitro. Our results confirmed the sustainable release of SDF-1α from the developed biomaterial promoting the migration and homing of human bone marrow mesenchymal stem cells (hBMMSCs) and hGMSCs. Moreover, the results of the osteogenic differentiation assay showed that SDF-1α delivery significantly enhanced osteogenic differentiation of hBMMSCs and hGMSCs and up-regulated the gene expression of osteogenic markers compared to the control group. In conclusion, the current study successfully developed a novel and effective treatment modality for craniofacial bone regeneration by recruiting the autogenous progenitor cells including hGMSCs. The developed niches can potentially lead to the development of a novel platform for targeted manipulation of in vivo microenvironment to achieve efficient and safe craniofacial cell reprogramming, which also will pave the road to determine the capacity of local hGMSCs’ contribution to in situ bone regeneration.